2023
DOI: 10.1037/rmh0000208
|View full text |Cite
|
Sign up to set email alerts
|

Socioenvironmental drivers of adolescent suicide in the United States: A scoping review.

Abstract: Suicide is an ongoing public health crisis among young people in the United States. Suicide rates in rural areas are often more than double rates in urban locales. Few reviews have examined the contextual place-based social, environmental, or economic factors that contribute to differences in mental health risks for young people. This scoping review aims to map the state of the evidence on socioenvironmental factors driving suicide risks in adolescents with a particular focus on rural America. A literature dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 97 publications
3
13
1
Order By: Relevance
“…Adolescents in rural areas have higher suicide fatality rates, as compared with adolescents who live in urban areas, and this rural/urban pattern is repeated for most racial/ethnic groups and for both boys and girls (although especially so for Indigenous adolescents and boys); see Figure A7 (Fontanella et al, 2015). This difference in suicide rates among adolescents within rural areas is associated with increased access to lethal means, primarily firearms (as we discuss above), and unmet need for mental health services (Runkle et al, 2022). However, while the rate of suicide death is higher for youth who live in rural areas, 8 in every 10 deaths due to suicide among adolescents occur among adolescents who live in urban areas, because more adolescents live in urban areas (CDC, 2023a).…”
Section: Variation By Geographymentioning
confidence: 83%
“…Adolescents in rural areas have higher suicide fatality rates, as compared with adolescents who live in urban areas, and this rural/urban pattern is repeated for most racial/ethnic groups and for both boys and girls (although especially so for Indigenous adolescents and boys); see Figure A7 (Fontanella et al, 2015). This difference in suicide rates among adolescents within rural areas is associated with increased access to lethal means, primarily firearms (as we discuss above), and unmet need for mental health services (Runkle et al, 2022). However, while the rate of suicide death is higher for youth who live in rural areas, 8 in every 10 deaths due to suicide among adolescents occur among adolescents who live in urban areas, because more adolescents live in urban areas (CDC, 2023a).…”
Section: Variation By Geographymentioning
confidence: 83%
“…Across studies, rates of completed suicides tend to vary across rural/urban classifications and area‐level socioeconomic factors. In particular, systematic reviews suggest that both rural areas and lower SES areas tend to show higher rates of completed suicides (Casant & Helbich, 2022; Runkle et al., 2022). Among youth, population‐based studies examining aggregated area‐level differences in suicide rates in the United States represent an important area of continuing research (Runkle et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The US Preventive Services Task Force recommends universal dual screening for both depression and suicide ideation among youth age 12 and older in primary care settings (Mangione et al., 2022). While research has identified other important risk factors for youth suicide including substance abuse, serious mental health issues, and consistent school or family problems, the four risk factors of hopelessness, suicide ideation, suicide planning, and suicide attempt are generally considered the most proximal indicators of suicide risk (Davidson & Linnoila, 2013; Klonsky et al., 2018; Runkle et al., 2022). Considering these risk factors collectively is essential for identifying youth in most acute need of suicide prevention services (Klonsky et al., 2018; Mangione et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations